2019
DOI: 10.1039/c9fo00199a
|View full text |Cite
|
Sign up to set email alerts
|

Fe and Zn in vitro bioavailability in relation to antinutritional factors in biofortified beans subjected to different processes

Abstract: The present work evaluated the effect of different processes in relation to mineral content and its bioavailability, as well as the effect of phytate and oxalate contents in biofortified beans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Figure shows the phytochemical composition of the raw and processed maize. Phytic acid is a chelating agent that reduces the bioavailability of calcium, magnesium, zinc, and iron, through the formation of insoluble complexes with them. , As shown in Figure , the phytate content of raw maize was determined to be 6.01 ± 1.43 mg/kg. Boiling and roasting significantly decreased ( P < 0.05) the phytate contents of maize to levels that were determined to be 2.80 ± 0.28 and 3.01 ± 0.01 mg/kg, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure shows the phytochemical composition of the raw and processed maize. Phytic acid is a chelating agent that reduces the bioavailability of calcium, magnesium, zinc, and iron, through the formation of insoluble complexes with them. , As shown in Figure , the phytate content of raw maize was determined to be 6.01 ± 1.43 mg/kg. Boiling and roasting significantly decreased ( P < 0.05) the phytate contents of maize to levels that were determined to be 2.80 ± 0.28 and 3.01 ± 0.01 mg/kg, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Plants and their products are the major sources of dietary oxalate, and it was reported that frequent consumption of foods with high levels of oxalate could inhibit calcium absorption and increase the risk of kidney stones . Foods with oxalate levels higher than 50 mg/100 g were categorized as oxalate-rich foods, while the lethal dose of oxalate for humans was reported to be 15–30 g. , As presented in Figure , the oxalate content of raw maize was determined to be 4.01 ± 1.43 mg/kg.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seed was hydrated in a container with a lid, using twice the weight of the legume material in drinking water, for a period of 24 hours at a temperature of 25-30°C, obtaining grain hydration of 60%. This stage facilitated the removal of the bean integument and also helped in the removal of the antinutritional factors of said legume such as trypsin inhibitor, protease inhibitor, phytic acid, among others (Abbas & Ahmad, 2018;Bezerra et al, 2019;Brigide et al, 2019).…”
Section: Second Stage -Moisturizing the Grainmentioning
confidence: 99%